The impact of age and body mass index on a bra sizing system formed by anthropometric measurements of Sichuan Chinese females. Issue 11 (1st November 2020) - Shi, Yuyuan; Shen, Hong; Taylor, Lindsey Waterton; Cheung, Vien
Abstract: Existing bra sizing systems are based only on bust and underbust girths, which do not guarantee an accurate fit or comfort for consumers. This study presents a comprehensive investigation of the impact of age and body mass index (BMI) on bra sizing systems, and the distributions of band and cup sizes based on anthropometric measurement data. The first four principal components were extracted by principal component analysis, and the factor loadings of age and BMI were found to be significant determinants of bra size along with 12 other variables. Furthermore, chi-square analysis revealed that bra size allocations were significantly influenced by age and BMI. Thus, we propose that age and BMI should be considered as auxiliary criteria for the bra sizing system. Taken together, these findings will be of value to designers and bra manufacturers in developing well-fitting bras for their target consumers, and to consumers for selecting well-fitting bras with confidence. Practitioner Summary: This study contributes to an understanding of how bra sizing systems are affected by age and BMI. This understanding is valuable to bra designers, manufacturers, and retailers, as it will enable the adjustment of bra sizes for different target markets and in turn improve consumer confidence in selecting proper fitting and comfortable bras.